A New EHR Training Curriculum and Assessment for Pediatric Residents - Stroup, Kathryn; Sanders, Benjamin; Bernstein, Bruce; Scherzer, Leah; Pachter, Lee M. (Applied Clinical Informatics, 2017)
Background Conventional classroom Electronic Health Record (EHR) training is often insufficient for new EHR users. Studies suggest that enhanced training with a hands-on approach and closely supported clinical use is beneficial.Objectives Our goals were to develop an enhanced EHR learning curriculum for Post Graduate Year 1 (PGY1) residents and measure changes in EHR skill proficiency, efficiency, and self-efficacy.Methods A novel three-phase, multimodal enhanced EHR curriculum was designed for a cohort of PGY1 residents. After basic training, residents began phase 1 of enhanced training, including demonstrations, live practice, and order set review. Phase 2 involved skills-oriented assignments, role playing, and medication entry. Phase 3 included shadowing, scribing histories, and supervised order entry. Residents' EHR skills and attitudes were measured and compared before and after the enhanced curriculum via proficiency test and a survey of efficiency and self-efficacy.Results Nineteen of 26 PGY1 residents participated in the study (73%). There was significant improvement in mean proficiency scores and two of the five individual proficiency scores. There were significant improvements in most efficiency survey responses from pre- to postintervention. For the self-efficacy presurvey, many PGY1s reported to be “very” or “somewhat confident” performing each of the five tasks, and perceptions did not improve or worsened on most postsurvey responses. The greatest resource was the time required to design and deliver the enhanced training.Conclusion An enhanced training curriculum along with a proficiency assessment was developed and described here. An enhanced training curriculum significantly improved PGY1 EHR efficiency and some measures of proficiency but not self-efficacy. This intervention may support improved EHR-related clinic workflows, which ultimately could enable residents and preceptors to prioritize patient care and time for clinical education.
Keywords: electronic health record; EHR; research; resident; EHR training; primary care; learner; assessment